2021
DOI: 10.1038/s41598-021-98657-7
|View full text |Cite
|
Sign up to set email alerts
|

A guide in lentiviral vector production for hard-to-transfect cells, using cardiac-derived c-kit expressing cells as a model system

Abstract: Gene therapy revolves around modifying genetic makeup by inserting foreign nucleic acids into targeted cells via gene delivery methods to treat a particular disease. While the genes targeted play a key role in gene therapy, the gene delivery system used is also of utmost importance as it determines the success of gene therapy. As primary cells and stem cells are often the target cells for gene therapy in clinical trials, the delivery system would need to be robust, and viral-based entries such as lentiviral ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 49 publications
0
9
0
Order By: Relevance
“…Clinically, ex vivo gene delivery to engineer therapeutic cells is bottlenecked by viral packaging limits of ∼5 kb (adeno-associated virus) to ∼10 kb (lentivirus) 43,44 . Compact genetic constructs are therefore a critical requirement for translational applications.…”
Section: Resultsmentioning
confidence: 99%
“…Clinically, ex vivo gene delivery to engineer therapeutic cells is bottlenecked by viral packaging limits of ∼5 kb (adeno-associated virus) to ∼10 kb (lentivirus) 43,44 . Compact genetic constructs are therefore a critical requirement for translational applications.…”
Section: Resultsmentioning
confidence: 99%
“…For example, while somatic gene transfer of both Cre and reporter gene sequences on the background of a conditional GEMM is resource-e cient, it may be limited due to lack vector tropism [40]. There are also payload considerations, with a ceiling at approximately 10 kbp for lentiviral vector, limiting the total number of reporter genes that are deliverable somatically [41]. Combining different transgenic alleles in a single composite animal through cross-breeding although straightforward in principle, requires prolonged and costly breeding.…”
Section: Discussionmentioning
confidence: 99%
“…First of all, we used a different packaging plasmid for LVs production: psPAX2 and pCMV-dR8.91 are both second generation plasmids and share similar architecture and gene compositions [ 38 ], but there could be differences in efficiency of virus production. For example, a recent study showed that pCMV-dR8.2 dvpr was able to stimulate a lentivirus production at least 7 times stronger than psPAX2 [ 39 ].However, since we always used the same titre of virus for transduction, this should not affect transduction efficiency per se. Further, the cell line used to produce the LVs might determine several characteristics of the EVs.…”
Section: Discussionmentioning
confidence: 99%